The impact of flipped teaching on EFL students’ academic resilience, self-directed learning, and learners’ autonomy - Izadpanah, Siros (Frontiers in Psychology, 2022)
Introduction This study attempted to investigate the impact of flipped teaching (FT) on EFL (English Foreign Language) students’ academic resilience (AR), self-directed learning (SDL), and learners’ autonomy (LA). Method To do this, the researcher selected 354 participants by the two-stage cluster sampling method. This research was quasi-experimental based on the pretest, and post-test, with experimental and control groups. Three questionnaires were administered to collect data. The questionnaires were analyzed using SPSS 24 software and inferred analysis of covariance (ANCOVA). Results The covariance study showed that FT significantly affected AR, SDL, and LA in learning with the help of the pre-test covariate variable (p<00.5). Also, the mean scores of students in the pre-test and post-test in the experimental group were significantly different. The mean scores of EFL students’ AR, SDL, and LA were higher through FT. It is suggested that school principals provide the ground for teachers’ participation in workshops on new teaching strategies so that teachers can benefit from new teaching approaches, including FT in the classroom. Discussion The study results showed that the mean AR of students in the experimental group’s post-test compared to the pre-test in both groups has significantly increased. The research findings indicate a positive effect of the flipped class on the levels of SDL. Based on the results, the flipped lesson class approach significantly affected the LA of English language learners as a foreign language. The findings of this study confirm previous relevant studies on the impact of flipped course classes on the LA of English language learners as a foreign language.